1998
DOI: 10.1002/chin.199831249
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Asymmetric Synthesis of 3‐Oxacarbacyclin and 3‐Oxaisocarbacyclin by a Common Enantioselective Deprotonation Based Route.

Abstract: hormones hormones U 1000 31 -249 Asymmetric Synthesis of 3-Oxacarbacyclin and 3-Oxaisocarbacyclin by a Common Enantioselective Deprotonation Based Route. -A new asymmetric synthesis of title compounds (XI) and (XIII), which are of medicinal interest, is presented. Key step is an enantioselective deprotonation of the prochiral ketone (I) with Li (R,R)-bis(phenylethyl)amide to the enol ether (III). -(VAULONT, I.; GAIS, H.-J.; REUTER, N.; SCHMITZ, E.; OSSENKAMP, R. K. L.; Eur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Previous studies have indicated that the selectivity of the chiral Li complex, when using base 4a-b for deprotonation, can be influenced by the formation of mixed aggregates between LiCl, formed by the reaction of the respective lithium complex with 1, and 4a-b, which is more reactive and selective than the monomer or dimer of 4a-b. 31 Simpkins and Bunn reported a substantial improvement in the stereochemistry of chiral basemediated deprotonation reaction products with the presence of added LiCl. 32 There are several reports that generate the 4ab.LiCl mixed heterodimeric Li-amide/LiCl complexes, that is, either from the direct addition of LiCl to 4a-b or the addition of BuLi to the 4a-b hydrochloride salt.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have indicated that the selectivity of the chiral Li complex, when using base 4a-b for deprotonation, can be influenced by the formation of mixed aggregates between LiCl, formed by the reaction of the respective lithium complex with 1, and 4a-b, which is more reactive and selective than the monomer or dimer of 4a-b. 31 Simpkins and Bunn reported a substantial improvement in the stereochemistry of chiral basemediated deprotonation reaction products with the presence of added LiCl. 32 There are several reports that generate the 4ab.LiCl mixed heterodimeric Li-amide/LiCl complexes, that is, either from the direct addition of LiCl to 4a-b or the addition of BuLi to the 4a-b hydrochloride salt.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…32 There are several reports that generate the 4ab.LiCl mixed heterodimeric Li-amide/LiCl complexes, that is, either from the direct addition of LiCl to 4a-b or the addition of BuLi to the 4a-b hydrochloride salt. 21,31,33 Thus, in the next experiment, 4a was treated first with LiCl (2 equiv) to generate 4a•LiCl followed by the sequential addition of 1 and 2. In this case, the dr of the product changed to 45:55.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation